Future Changes in Oceanography and Biogeochemistry Along the Canadian Pacific Continental Margin - Holdsworth, Amber M.; Zhai, Li; Lu, Youyu; Christian, James R. (Frontiers in Marine Science, 2021)
Model projections of ocean circulation and biogeochemistry are used to investigate large scale climate changes under moderate mitigation (RCP 4.5) and high emissions (RCP 8.5) scenarios along the continental shelf of the Canadian Pacific Coast. To reduce computational cost, an approach to climate downscaling was developed that uses atmospheric climatologies with augmented winds to simulate historical (1986-2005) and future (2046-2065) periods separately. The two simulations differ in initial and lateral open boundary conditions. For each simulation, the daily climatology of surface winds in the driving model was augmented with high-frequency variability from an atmospheric reanalysis product. The `time-slice' approach was able to reproduce the observed climate state for the historical period. Sensitivity tests confirmed that the high frequency wind variability plays an essential role in freshwater distribution in this region. Projections suggest that sea surface temperature will increase by 1.8°C to 2.4°C and surface salinity will decrease between -0.08 and -0.23 depending on whether a moderate or high emissions scenario is used. Stratification increases throughout the region and there is some evidence of nutrient limitation near the surface. Primary production and phytoplankton productivity (chlorophyll) also increase. Density surfaces are relocated deeper in the water column and this change is mainly driven by surface heating and freshening rather than dynamical `uplift' of isopycnal surfaces. Changes in saturation state are mainly due to anthropogenic CO2 with minor contributions from solubility and remineralization. There is little difference between RCP 4.5 and RCP 8.5 with regard to projections of deoxygenation and acidification. The depths of the aragonite saturation state and the oxygen minimum zone are projected to become shallower by 100m and 75m respectively. Extreme states of temperature, oxygen and acidification are projected to become more frequent and more extreme, with the frequency of occurrence of [O2] less than 60 mmol m-3 expected to approximately double under either scenario.